Commitment or not? Creator's quality strategies with uncertain market in reward-based crowdfunding. Issue 17 (2nd September 2022) - Gao, Qian; Guo, Xiaolong; Yang, Feng; Yu, Yugang
ABSTRACT: This paper studies a creator's quality commitment strategies with uncertain demand when the creator lacks setup funding and chooses crowdfunding to finance. Facing uncertain demand, the creator may or may not choose to make a quality commitment. Conventional wisdom indicates that the strategy of committing to a certain quality outperforms the no-commitment strategy by eliminating the consumers' strategic behavior of delaying purchases. We build a two-period model consisting of crowdfunding and spot sales periods, a creator lacking setup funding, and consumers with heterogeneous valuations for the product. When considering the creator's setup cost and market uncertainty, we find, counterintuitively, that making no quality commitment to consumers can be more profitable for the creator because of the advantage of flexibility. Moreover, our analysis shows that when the creator's setup cost is high enough, the profit-maximising creator will make a quality commitment to consumers and offer a higher-quality product than when making no commitment. Also, we show that the product quality increases with the market uncertainty under certain conditions. In addition, we find that the creator should finance through crowdfunding only when the setup cost is less than a threshold, and the threshold increases with market uncertainty.